A Study on Neural Network Method for In-body Implantable Device Localization - Dmitrieva, Daria; Anzai, Daisuke; Kirchner, Jens; Fischer, Georg; Wang, Jianqing (IEICE Society conference, 2022)
Keywords: WCE; localization; RSSI; implant; ML; phantom

ETSI SmartBAN Architecture: The Global Vision for Smart Body Area Networks - Hamalainen, Matti; Mucchi, Lorenzo; Girod-Genet, Marc; Paso, Tuomas; Farserotu, John; Tanaka, Hirokazu; Anzai, Daisuke; Pierucci, Laura; Khan, Rida; Alam, Muhammad Mahtab; Dallemagne, Philippe (IEEE Access, 2020)
This paper presents a condensed review of the European smart body area network (BAN) standardization work and its already published standards. The work is carried out under the ETSI Technical Committee (TC) SmartBAN. The goal of ETSI TC SmartBAN is to define and develop new European BAN standards; fostering the successful market adoption of wireless BAN technology by providing a standardized way to bring new interoperable products into the health, medical, sport, leisure and IoT markets, targeting to global exploitation. TC SmartBAN covers wireless communications, especially the physical and medium access control layers, associated security, semantic interoperability and open data representation, which are necessary features in the data transmissions, as well as building blocks of the future smart coordinator. The use of smart coordinator centralizes the network intelligence to the hub, which enables implementation of simple nodes. The SmartBAN approach will be computationally light, and it supports reliable operations across heterogeneous networks. Due to the semantic approach in all functional levels, SmartBAN also supports high interoperability. For emergency traffic, SmartBAN provides different priority classes and fast channel access associated with a low latency. Novel concept adopted in the SmartBAN for high-priority traffic is a multi-use channel access, which can also improve the spectral efficiency. Not only on-body nodes and applications, TC SmartBAN is considering in-body communications for capsule endoscopy. In addition, SmartBAN collaborates with other standardization groups, such as oneM2M and AIOTI, to widen the impact of its work.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Interoperability; medium access control; open data format; physical layer; semantic interoperability; wireless